Aiming for validity: The experience of conflicts in legitimacy judgments in esports actors and new grassroots activism - Cestino-Castilla Joaquin; Macey Joseph; McCauley Brian (Germany, 2022)
Esports is a phenomenon which continues to grow in socio-cultural and economic importance, yet it remains at the edges of mainstream society. To date, there have been few works which address the topic in terms of legitimacy, particularly the micro-processes of legitimization. Given that the esports system is one which currently operates outside wider societal practices, the lived experiences of actors in the ecosystem can offer valuable insights into the world of esports. This research employs IPA in order to understand how actors in organized grassroots esports movements make sense of their individual experiences and actions. A series of novel contributions are provided by this work. First, micro-level theories of legitimacy are applied to a phenomenon which has recently come to mainstream attention, one which is at the same time a business and a culture. Second, it is the first, in our knowledge, to apply a qualitative methodology to the explicit issue of legitimacy in esports. Third, it adds to theories of legitimacy and institutional change by providing empirical insights into the circumstances in which the experience of conflicts in legitimacy judgments independently mobilizes actors, shaping collective action into grassroots activism efforts. Finally, it highlights tensions between international success and the foundations of grassroots esports.
Proceedings of the 5th International GamiFIN Conference